White Cultural Imperialism and the New Zealand Criminal Justice System: Importance of Insider Voices - Martin, Jessica (New Zealand Sociology, 2023)
In New Zealand, Māori women and men make up a disproportionate amount of the prison population, reflecting what Indigenous scholars have termed the era of the hyper-incarceration of Indigenous people. Using Tracey McIntosh’s conceptualisation of the violence continuum and Donna Awatere’s framework of White cultural imperialism, this article examines the colonial past and current state of the New Zealand criminal justice system with a particular focus on how crime is framed in New Zealand public discourse. This article offers insight into how Whiteness is operationalised in re-enforcing Māori as the criminal Other. Voices of incarcerated or formerly incarcerated Indigenous and non-Indigenous people offer counter-narratives to dominant frames of criminality advanced by the state and offer opportunities for moving forward.